Handbook on Craniofacial Superimposition The MEPROCS Project - Damas, Sergio; Cordón, Oscar; Ibáñez, Oscar (Springer International Publishing : Imprint: Springer, 2020)
This open access book is the first comprehensive guide to a new soft computing technique which is used in complex forensic cases. The chapters include detailed technical and practical overviews, and discussions about the latest tools, open problems and ethical and legal issues involved. The book will be of interest to researchers and practitioners in forensic medicine and computational intelligence. The book is closely associated with a successful research initiative, MEPROCS (New Methodologies and Protocols of Forensic Identification by Craniofacial Superimposition). The project collaborators were: S. Damas, O. Ibáñez, M.I. Huete, T. Kahana, C. Wilkinson, E. Ferguson, C. Erolin, P.T. Jayaprakash, R. Jankauskas, F. Cavalli, K. Imaizumi, R. Vicente, D. Navega, E. Cunha, A.H. Ross, E. Veselovskaya, A. Abramov, P. Lestón, F. Molinero, E. Ruiz, F. Navarro, J. Cardoso, F. Viegas, D. Humpire, R. Hardiman, J. Clement, A. Valsecchi, B.R. Campomanes-Alvarez, C. Campomanes-Alvarez, A.S.Çağdır, T. Briers, M. Steyn, M. Viniero, D.N. Vieira, and O. Cordón.